Toxicities comparison of rotenone and acetone extract of Tephrosiavogelii and Derris trifoliate against Solenopsis invicta - Dong-Mei Cheng; Cong-Ling Huang; Wei-Sheng Li; Yong-Qing Tian; Run-Qian Mao; Zhi-Xiang Zhang (Sociobiology, 2015)
The high rotenone content and the rotenone crude extract of Tephrosia vogelii and Derris trifoliata were evaluated for its efficacy in the control of red imported fire (RIFA), Solenopsis invicta under both laboratory and field conditions. The acetone extracts of D. trifoliata roots and T. vogelii leaves exhibited strong toxicity to macroergate and micrergate of RIFA. When active ingredients of the crude extracts were convert to rotenone, the activity of the acetone extracts were higher than that of rotenone technical material. At the same time, the extracts showed significant inhibitory effect on walking ability and grasping ability of worker ants and stronger than the effect of 98.6% rotenone technical material. Under field conditions, the 0.01% rotenone-bait, formulated with the acetone extract of D. trifoliata roots and T. vogelii leaves, had the same control effect on RIFA as that of 0.01% fipronil-bait when treated after 30 d. The bait formulated with the extract of D. trifoliata exhibited quicker and higher effect on RIFA than that of rotenone technical material. It was showed that the acetone extracts of D. trifoliata roots and T. vogelii leaves are able to control S. invicta under both laboratory and field conditions and can be used as an effective agent against RIFA.